PCR Methods for Rapid Identification and Characterization of Actinobacillus seminis Strains - Appuhamy, S. (American Society for Microbiology, 1998)
Twenty-four isolates of Actinobacillus seminis were typed by PCR ribotyping, repetitive extragenic palindromic element (REP)-based PCR, and enterobacterial repetitive intergenic consensus (ERIC)-based PCR. Five types were distinguished by REP-PCR, and nine types were distinguished by ERIC-PCR. PCR ribotyping produced the simplest pattern and could be useful for identification of A. seminis and for its differentiation from related species. REP- and ERIC-PCR could be used for strain differentiation in epidemiological studies of A. seminis.